HIFEMA : TINJAUAN KLINIS DAN KLASIFIKASI - Imtinan Khoirunnisa; Carissa Aprilia Y; Fadilah Alwiyah; Regita Dwi M; Rani Himayani; Putu Ristyaning Ayu Sangging (CV. Jasa Sukses Abadi, 2023)
Accumulation of blood in the anterior chamber of the eye called hyphema. A hyphema usually caused by blund trauma to the eye. It can also occur as a result of surgery inside the eye or abnormal blood vessels inside eye. Bleeding, eye pain, blurry or distorted vision, and light sensitivity is the symptoms of hyphema. The treatment are encouraging the blood, treat elevation incraocular pressure, bed rest is recommended. Also, patient of hyphema can also kept head in elevatd position during sleep and protect the eye with a shield. Steroid eye drops usually prescribed to limit inflammation, dilating drops, and reduce the pain. The last treatment is surgery with purpose to remove the blood. Prognosis of hyphema depends on size, small sized have a good prognosis. But, patient whose have eyes undergo rebleding have bad prognosis because they have larger sized of hyphema.